Immunological regulation of the active fraction from Polygonatum sibiricum F. Delaroche based on improvement of intestinal microflora and activation of RAW264.7 cells. (15th July 2022) - He, Yanfei; Huang, Lin; Jiang, Ping; Xu, Guangpei; Sun, Taotao
Abstract: Ethnopharmacological relevance: Polygonatum sibiricum, known as "Huangjing" in Chinese traditional medicine, of which functions include invigorating Qi and nourishing Yin, tonifying spleen and kidney, which are considered to replenish energy, and strengthen immunity. However, both the active components and mechanism of the immune-enhancing effect of Polygonatum sibiricum have not been clarified. Aim of the study: To evaluate the immunoregulation effects of PSE30 ( Polygonatum sibiricum ethanol 30) and PSE75 ( Polygonatum sibiricum ethanol 75). The gut microbial and activation of RAW264.7 cells were also evaluated for exploring the mechanism of PSE75. Materials and methods: Female ICR mice were randomly divided into different groups, which were pretreated with 0.9% saline, Yupingfeng granules, different dosage of PSE30 or PSE75. And the immunosuppressed mice model was constructed using cyclophosphamide. And the total duration of the experiment was 15 d. After that, the serum Immunoglobulins G (IgG) and Immunoglobulins M (IgM) antibody, regular blood testing, assessment of natural killer cell activity, and histological observation of spleen in immunosuppressed mice were measured to evaluate the immunoregulation effects of PSE30 and PSE75. Besides, effects of PSE75 on gut microbial were evaluated using 16s rRNA sequence. And the mRNA expression and cytokine secretion of RAW264.7 cell were evaluated to analyze the immunoregulation mechanism of PSE75. Results: The content of serum IgG, IgM was significantly elevated by PSE75 ( P ＜0.05, P ＜0.001). The NK cells killing activity in splenocytes against K562 cells induced by PSE30, and PSE75 was pronounced higher than that of the model group ( P  < 0.05). Both mRNA expression of Th1 molecular markers including interleukin (IL)-2, interferon (IFN)-γ, and signal transducers and activators of transcription (STAT) 4, and Th2 molecular markers including IL-4 in splenocytes were markedly enhanced by PSE30, and PSE75 ( P  < 0.05, P  < 0.01, or P  < 0.001). Besides, the result of 16s rRNA sequence indicated that PSE75 could recover the gut microbial community disturbed by cyclophosphamide. PSE75 could markedly promote the secretion of IL-6, IL-10, and IL-12 p40 from RAW264.7 cell ( P ＜0.01, or P ＜0.001). Conclusions: PSE75 was proved to be a more promising immunomodulation agent, of which may enhance the immunity of immunosuppressed mice by improving gut microbial and activating macrophages. And PSE75 could be developed as a good immune booster in the future. Graphical abstract: Image 1